Experimental model of acute osteomyelitis in rats - Medeiros, Aldo Cunha; Rêgo, Amália Cínthia Meneses; Macedo-Filho, Robson; Araújo-Filho, Irami; Azevedo, Ítalo Medeiros de; Medeiros, Vítor Brasil (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2014)
Purpose: The aim of this study was to characterize a model of acute osteomyelitis and the best time for bacterial recovery. Method: A segmental defect was surgically created in the rat femur, and contaminated with bacteria. The animals were allowed to recover in individual cages while the contamination progressed to an acute infection. At a later point in time, the defect was surgically debrided and washed with saline. To implement this model, the experiment was performed to determine the best time from contamination to the moment that would reliably result in acute infected osteomyelitis. The number of recovered bacteria was measured in 18 rats (n=6/group) as a function of inoculum of Staphylococcus aureus (106 CFUs) and 3 times from contamination (3 days, 1week or 3 weeks). Results: Recovered bacteria occurred in all animals after 3 days, 1 week and 3 weeks. Bacterial inoculums time from each contaminated group had a significant effect on the mean of the number of recovered CFUs of bacteria. The mean log10 CFUs of recovered bacteria for each inoculum peaked at 1 week after contamination (7.84±0.22 log10CFU). Consequently, the mean log10 CFUs of bacteria recovered at 1 week was significantly greater than the amount of bacteria recovered after 3 days (4.63±0.10) and 3 weeks (6.09±0.14) (p<0.001). Conclusion: This model of acute osteomyelitis was well characterized. Our data confirmed that 1 week after contamination was the optimal time to study bacterial recovery. We can infer that this model was viable and allows us to perform further studies on treatment of osteomyelitis with vetorized antimicrobials and other regimens of antibiotic therapy.